Hubungan Koordinasi Mata Tangan, Kekuatan Otot Lengan, Keseimbangan Terhadap Ketepatan Shooting dalam Olahraga Petanque - Safitri, Adella Ika; Yusfi, Herri; Solahuddin, Soleh; Bayu, Wahyu Indra; Rasyono, Rasyono (Universitas Hamzanwadi, 2024)
The problem in this study is that there are students who do not have good hand eye coordination, arm muscle strength and balance, this can be seen when students shoot the ball not right on target and not directed. This study aims to determine whether there is a relationship between hand eye coordination, arm muscle strength, and balance on the results of shooting petanque. This type of research is quantitative with correlational research. Data analysis techniques with simple and multiple correlation tests using SPSS 27. The population of this study were 60 Sriwijaya University's penjaskes students. The sample of this study was 34 Sriwijaya University penjaskes students, the samples taken were only students who took petanque courses in semester 7. This study used tennis ball throwing and catching test instruments, pull and push dynamometer test kits, standing stork tests and petanque shooting games. The results showed a correlation between hand eye coordination, arm muscle strength and balance on petanque shooting results with a significant value of 0.00 and a value of R = 0.678. Conclusion There is a relationship between hand eye coordination, arm muscle strength and balance to the results of shooting petanque students of Penjaskes Sriwijaya University.